Emerging States and Economies Their Origins, Drivers, and Challenges Ahead - Shiraishi, Takashi; Sonobe, Tetsushi (Emerging-Economy State and International Policy Studies,, 2019)
This open access book asks why and how some of the developing countries have "emerged" under a set of similar global conditions, what led individual countries to choose the particular paths that led to their "emergence," and what challenges confront them. If we are to understand the nature of major risks and uncertainties in the world, we must look squarely at the political and economic dynamics of emerging states, such as China, India, Brazil, Russia, and ASEAN countries. Their rapid economic development has changed the distribution of wealth and power in the world. Yet many of them have middle income status. To global governance issues, they tend to adopt approaches that differ from those of advanced industrialized democracies. At home, rapid economic growth and social changes put pressure on their institutions to change. This volume traces the historical trajectories of two major emerging states, China and India, and two city states, Hong Kong and Singapore. It also analyzes cross-country data to find the general patterns of economic development and sociopolitical change in relation to globalization and to the middle income trap.